Implementation of Bhinneka Tunggal Ika Mottoes in Social and State Life - Sandy Gunawan; Diki Zakaria; Ranny Caroline; Tria Harjanti; Jason Tandani (International Journal of Business and Quality Research, 2024)
The motto "Bhinneka Tunggal Ika," which affirms the values of pluralism and unity in the context of cultural, religious, and ethnic diversity in Indonesia, has become an undeniable moral foundation in building the nation's identity. Although officially recognized as the spirit of nationhood, the implementation of Bhinneka Tunggal Ika still faces a number of complex challenges in Indonesia's diverse society. In this context, this article aims to conduct an in-depth analysis of these problems, explore the root causes that hinder the implementation of this motto, and formulate concrete solutions to strengthen awareness of diversity and promote social harmony in Indonesia. Taking into account the negative impacts of suboptimal implementation of this motto, strategic measures can be designed to foster inclusiveness, respect for differences, and build inter-ethnic solidarity across the country. Through this approach, it is hoped that there will be positive changes in building a more united, just, and harmonious society, which makes Bhinneka Tunggal Ika not only an empty motto, but as the main pillar in maintaining the unity and unity of the Indonesian nation.